Պոնտոսի Միհրդատ VI Եվպատոր թագավորը նաև հայոց արքա - Բաբկեն Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Изучение труда Мовсеса Хоренаци и ряда других первоисточников показывает, что деятельность знаменитого понтийского царя Митридата VI Евпатора,в частности, описание его известного похода в страны Малой Азии и Грецию с целью приостановить экспансию римлян и создать великую эллинистическую державу приписывается армянскому царю Арташесу. The study of Movses Khorenatsi's work and various other sources shows that the acts of the famous Pontian king, Mithridates VI Eupator, have also been attributed to the Armenian king Artashes, particularly in the description of his well known march into the Hellenistic states of Asia Minor and Greece, which were intended to halt Roman expansion into the East, and to create a great Hellenistic realm.
Keywords: History; Ancient History; D History